The Role of the Consensus Approach to Governance In Accordance With the Decisions of the Basel Committee on Banking Supervision (BCBS) In Improving the General Banking Performance. (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2021)
PURPOSE: Identify the extent of the impact of consensual governance on the general banking performance in a sample of private commercial banks.The problem: The banking sector in the world has witnessed in recent years many developments in line with the changing needs of customers, and in light of globalization, Iraqi banks have found themselves obligated to keep pace with those developments related to banking services provided to customers, as well as the mechanisms adopted to manage the banking business, foremost of which is the adoption of governance mechanisms because of their Positive effects indicated by a number of foreign studies and confirmed by the Basel Committee on Banking Supervision (BCBS). Therefore, researchers see the need to study the extent of the reflection of the consensus approach to governance in improving the general performance of Iraqi private commercial banks.Objective: The aim of the current study is to uncover the vital and important role of consensual governance in upgrading the general banking performance in private commercial banks, the research sample.Design / Methodology / Approach: The selection fell on four commercial banks that occupy an important position among the private commercial banks and are considered committed to institutional governance mechanisms (according to the Central Bank of Iraq report for the year 2019). The research sample was chosen, which consisted of (40) individuals from senior management in banks, the research sample, and by (10) individuals from each bank. Correlation coefficient, regression coefficient), in addition to using the normal distribution test and exploratory factor analysis to test the validity of the approved measures and choose the appropriate statistical analysis. The outputs of statistical programs (SPSS V.23), (Excel V. 2012) were relied on.Results: The study reached a set of conclusions, the most prominent of which is the significant impact of consensual governance on the general banking performance of banks, the research sample as well as presenting a set of ideas and visions that contribute to raising the level of readiness of private commercial banks to implement and benefit from governance.